DETERMINANTS OF SHARIA RETIREMENT FINANCIAL PLANNING MILLENNIAL GENERATION IN INDONESIA - Nurul Hasanah; Ratna Juwita; Aprilia Nur Fitriana; Muthi'ah Rahmah Syahidah; Ricardo Marcell Dimas Djiwandono (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
The research was motivated by a phenomenon where many retirees in Indonesia could not enjoy a prosperous retirement, and some even had to continue working to meet their living needs. Based on this phenomenon, financial planning is very important for well-being in old age and needs to be done early when someone is still in their productive period. However, the millennial generation, as the largest population of productive age, does not yet have financial planning for retirement. In line with Indonesian society, which is predominantly Muslim, the goal of finance is not only for peace in this world but also in the afterlife. For this reason, the research aims to analyze the factors determining the millennial generation's Islamic retirement financial planning. The research method used is SEM-PLS with the variables studied including financial literacy, clarity of retirement goals, and financial attitudes as mediating variables. The research results show that financial literacy and clarity of retirement goals directly influence financial attitudes, but do not influence sharia retirement financial planning. Apart from that, financial attitudes also show that the results do not affect sharia retirement financial planning. Financial attitudes do not mediate the influence of financial literacy and clarity of retirement goals on Sharia retirement financial planning. The results of this research can be used as consideration for the government and pension fund companies in determining strategies and policies to improve the welfare of the Indonesian population.